Dualisme Administrasi Pemerintahan di Daerah Perbatasan: (Studi Kasus di Perbatasan Kabupaten Kampar dan Rokan Hulu) - Candra Asmara; Muslim (Nakhoda: Jurnal Ilmu Pemerintahan, 2015)
Regional dissociation or area forming progressively more than of when ratifying of Law Number 22 Year 1999 about Area Governance which later; then revised to become the Law Number 32 Year 2004 is finally revised again become the Law of Number 23 Year 2014. Area forming [in] early independence proclaimedly of independence on 17 August 1945, Indonesia have 8 province, that is Sumatra, Borneo, West Java, Central Java, East Java, Sulawesi, Small Sunda And Moluccas. Until year 2014 in Indonesia have there are 34 Provinsi and 524 Sub-Province / town. Cause factors of the happening of dualisme of public administration is conflict of state line at autonomous era of area in Province Riau, specially between Kampar Sub-Province with the Sub-Province of Rokan Hulu;Upstream is ill defined of coordinate point state line, policy and wrong government administration practice, importance of capital owner, and importance politic. the state line Conflict affect to resident status society becoming double of administration, suffrage society partly becoming to lose, and Conflict of Horizontal and Governmental of public servant. Policy of is set in regional dissociation of Kampar Sub-Province with the Sub-Province of Rokan Hulu ;Upstream of Province Riau require to study various aspect, so that [do] not peep out the regional conflict pasca dissociation. All of importance (stakeholders) expected can realize the society association, and prioritize the society importance from other importances, so that dualisme of public administration can be avoided and existence of clear staus demografi to society of exist in frontier of Sub-Province of Kampar and Sub-Province of Rokan Hulu;Upstream, especially 5 countryside becoming problems in the state line area.